Remoção de nitrogênio e matéria orgânica em um reator de leito estruturado em escala piloto, submetido à aeração intermitente, no tratamento de esgoto sanitário - Barbosa, Talita Aleixo (2023)
This study aimed at evaluating the organic matter and nitrogen removal, simultaneously, from domestic sewage, in a Structured Bed Reactor subjected to intermittent aeratin (SBRIA), on a pilot scale, installed at ETE-Bortolan, in Poços de Caldas - MG. The SBRIA, operated with a hydraulic detention time (TDH) of 10 hours, has a cylindrical shape, with an internal diameter of 1.8 m and a total height of 5.1 m (useful height of 4.9 m). The total volume of the reactor is 12.3 m³ and the useful volume is 8.4 m³, generating a bed porosity of 66%. Despite the predominantly domestic characteristic, the input concentrations of oxidized nitrogenous compounds, mainly nitrate (N-N), indicated the presence of industrial effluent, which probably resulted in an increase in solids present at the reactor outlet and, consequently, the necessity to simulate a decantation unit to achieve better efficiencies. The average COD removal efficiency without sedimentation was 54 ± 29% and 77 ± 10% with sedimentation. The total nitrogen (NT), in turn, had an average removal efficiency of 54 ± 29%, with the low total Kjeldahl nitrogen (NTK) removal efficiency, mainly influenced by the organic nitrogen (N-org) portion, being the main limiting factor. Using the N-org data with simulation of a settling unit, the NT removal efficiency increased to 74 ± 11%. It is observed that, for the removal efficiencies without sedimentation, the standard deviation indicates the high instability caused by the solids. Even with the momentary instability possibly generated by the presence of toxic compounds for microorganisms, the system showed resilience and was able to recover, later showing high removal efficiencies and indicating yet another advantage of SBRIA. As for the already known advantages, it was possible to confirm the possibility of simultaneous nitrification and denitrification (NDS) through intermittent aeration on a pilot scale, reducing costs with oxygenation, in addition to the dispensability of adding an alkalizing substance. On the other hand, given the composition of the effluent, it was not possible to dispense the use of a clarification unit. Despite this, compared to other treatments, such as conventional activated sludge, the amount of solids in the effluent is quite reduced, allowing for savings with the reduction in the size of the clarification unit.